Lack of Association between the BIM Deletion Polymorphism and the Risk of Lung Cancer with and without EGFR Mutations. Issue 1 (January 2015) - Ebi, Hiromichi; Oze, Isao; Nakagawa, Takayuki; Ito, Hidemi; Hosono, Satoyo; Matsuda, Fumihiko; Takahashi, Meiko; Takeuchi, Shinji; Sakao, Yukinori; Hida, Toyoaki; Faber, Anthony C.; Tanaka, Hideo; et al.
<x xml:space="preserve">Abstract</x> Introduction: The BIM deletion polymorphism in intron 2 was found in a significant percent of the Asian population. Patients with epidermal growth factor receptor (EGFR) mutant lung cancers harboring this BIM polymorphism have shorter progression free survival and overall response rates to EGFR tyrosine kinase inhibitors. However, the association between the BIM deletion polymorphism and lung cancer risk is unknown. Methods: The BIM deletion polymorphism was screened by polymerase chain reaction in 765 lung cancer cases and 942 healthy individuals. Results: Carriers possessing one allele of the BIM polymorphism were observed in 13.0% of control cases and 12.8% of lung cancer cases, similar to incidence rates reported earlier in healthy individuals. Homozygote for the BIM polymorphism was observed in four of 942 healthy controls and three of 765 lung cancer cases. The frequency of the BIM deletion polymorphism in lung cancer patients was not related to age, sex, smoking history, or family history of lung cancer. The BIM deletion polymorphism was found in 30 of 212 patients with EGFR wild type lung cancers and 16 of 120 patients with EGFR mutant lung cancers. The frequency of the BIM polymorphism is similar between cancers with wild type EGFR and mutated EGFR (p = 0.78). Conclusion: The BIM deletion polymorphism was not associated with lung cancer susceptibility. Furthermore, the BIM polymorphism is not associated with EGFR mutant lung cancer.